Self-medication practice in pregnant women from central Mexico - Angel Josabad Alonso-Castro; Alan Joel Ruiz-Padilla; Yeniley Ruiz-Noa; Clara Alba-Betancourt; Fabiola Domínguez; Lorena Del Rocío Ibarra-Reynoso; Juan José Maldonado-Miranda; Candy Carranza-Álvarez; Christian Blanco-Sandate; Marco Antonio Ramírez-Morales; Juan Ramón Zapata-Morales; Martha Alicia Deveze-Álvarez; et al. (Elsevier, 2018)
Self-medication during pregnancy represents a serious threat for mother and child health. The objective of this study was to evaluate the prevalence and the factors associated with self-medication among Mexican women living in the central region of Mexico. This is a descriptive interview-study of 1798 pregnant women or women who were pregnant no more than 3 years ago, when the interview was carried out. Data analysis was carried out with chi-square analysis and odds ratio. The prevalence of self-medication (allopathic drugs, medicinal plants, and other products, including vitamins, food supplements, among others) was 21.9%. The factors associated (p < 0.05) with self-medication were: higher education (college and postgraduate), smoking, and consumption of alcohol. Smoking was the strongest factor (OR: 2.536; 1.46-4.42) associated to self-medication during pregnancy, followed by consumption of alcohol (OR: 2.06; 1.38-3.08), and higher education (OR: 1.607; 1.18-2.19). Medicinal plant consumption was associated with nausea, constipation, migraine, and cold (p < 0.05), whereas he self-medication of allopathy was associated with gastritis and migraine (p < 0.05). Self-medication was influenced mainly by a relative or friend, who recommended the use of herbal medicine/allopathic medication. Two of the most common medicinal plants (arnica and ruda) here informed are reported to induce abortion or toxicity during pregnancy. The findings showed that self-medication (medicinal plants and allopathic medication) is a common practice among pregnant women from central Mexico. Adequate counselling of pregnant women by healthcare professionals about the potential risks of self-medication with herbal medicine and allopathic drugs during pregnancy is strongly warranted. Keywords: Self-medication, Pregnancy, Allopathy, Medicinal plant